2019
DOI: 10.1371/journal.pone.0217984
|View full text |Cite
|
Sign up to set email alerts
|

Depression is a major risk factor for the development of dementia in people with lower urinary tract symptoms: A nationwide population-based study

Abstract: Background/Objectives Studies have shown a strong relationship between depression and dementia. Lower urinary tract symptoms (LUTS) were reported to be independently associated with depression and dementia. However, the relationship between depression and cognitive dysfunction in patients with LUTS is not well characterized. Method We conducted a matched cohort study by using a one-million population-based dataset in Taiwan. A total of 15,944 patients with LUTS aged 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…During the endoscopic standard procedures, the patient who undergoesndergoes regional anesthesia is awake, and the reproductive organs will be exposed, so that the patient is more likely to show anxiety and stress and other emotions. 39 Complementary therapies to decrease the pain and anxiety during endoscopic standard procedures are becoming more popular day by day. These therapies include music, transcutaneous electrical nerve stimulation, acupuncture, and auricular acupressure.…”
Section: Dovepressmentioning
confidence: 99%
“…During the endoscopic standard procedures, the patient who undergoesndergoes regional anesthesia is awake, and the reproductive organs will be exposed, so that the patient is more likely to show anxiety and stress and other emotions. 39 Complementary therapies to decrease the pain and anxiety during endoscopic standard procedures are becoming more popular day by day. These therapies include music, transcutaneous electrical nerve stimulation, acupuncture, and auricular acupressure.…”
Section: Dovepressmentioning
confidence: 99%
“…The association between the brain (dementia and depression) and bone is a bidirectional communication that is evidenced by several clinical observations [7][8][9][10][11][19][20][21][22] and experimental studies [23][24][25][26][27][28][29][30]. Two bone cellderived modulators, osteoblast-derived osteocalcin and lipocalin 2, can affect behavioral and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Depression was an associated factor for dementia, especially among people aged 45–64 years (midlife) [14]. Depression was a major risk factor for the onset of subsequent dementia in patients with lower urinary tract symptoms [11]. Those who had a history of depression earlier in life had a higher risk of dementia than those who did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A nationwide population-based study demonstrated that depression is a major risk factor for the dementia in patients with LUTS, and early screening and interventions for depression in patients with LUTS may play an important role in maintaining cognitive function. 6 In addition, Chiang et al 7 demonstrated that LUTS increased the risk of dementia in Chinese population.…”
Section: Introductionmentioning
confidence: 99%